The Role of the Introductory Matter in Bilingual Dictionaries of English and Arabic - Al-Ajmi, Hashan (Lexikos, 2001)
Abstract: Monolingual and bilingual dictionaries for learners of English as foreign language differ from each other in many aspects. Among the differences are the types of information a dictionary provides outside the A?Z word list, especially in its introductory matter. Yet, dictionary introductions have been referred to rather peripherally in the literature on dictionary users and uses. Within the context of lexicographic practice, this study aims to outline the differences between EFL learner’s dictionaries and bilingual English?Arabic dictionaries, and to determine to what extent a given set of popular dictionaries provide varied and sufficient information in their introductions. Three categories of dictionaries will be the subject of comparison: EFL dictionaries, European bilingual dictionaries, and bilingual dictionaries in the Arab world. Keywords: BILINGUAL DICTIONARY, INTRODUCTORY MATTER, ENGLISH?ARABIC, EFL LEARNER’S DICTIONARY, ORIENTALIST DICTIONARY Opsomming: Die rol van die inleidende gedeelte in tweetalige woordeboekevan Engels en Arabies. Eentalige en tweetalige woordeboeke vir aanleerders vanEngels as vreemde taal verskil in baie opsigte van mekaar. Een van die verskille is die tipes inligtingwat ’n woordeboek buite die A–Z-woordelys verskaf, veral in die inleidende gedeelte. Tog isdaar slegs in die verbygaan na woordeboekinleidings in die literatuur oor woordeboekgebruikersen -gebruik verwys. Hierdie studie het dit ten doel om, binne die konteks van die leksikografiesepraktyk, die verskille uit te stippel tussen EVT-aanleerderswoordeboeke en tweetalige Engels–Arabiesewoordeboeke, en te bepaal in watter mate ’n gegewe groep gewilde woordeboeke veelsoortigeen genoegsame inligting in hul inleidings verskaf. Drie kategorieë woordeboeke sal die onderwerpvan hierdie vergelyking vorm: EVT-woordeboeke, Europese tweetalige woordeboeke entweetalige woordeboeke binne die Arabiese wêreld. Sleutelwoorde: TWEETALIGE WOORDEBOEK, INLEIDENDE GEDEELTE, ENGELS–ARABIES, EVT-AANLEERDERSWOORDEBOEK, ORIËNTALISTEWOORDEBOEK